Estudios sobre consistencia en las ideas de los alumnos en ciencias - Oliva Martínez, José Mª (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 1996)
This article reviews the different lines of research related to the studies about «consistency» in the ideas as expressed by students, a highly interesting concept both from the theoretical and practical standpoints.